Agenda-Setting Through the Television Programming Schedule: An Examination of Major League Baseball on Fox. Issue 3 (1st October 2016) - Fortunato, John A.
ABSTRACT: The core concept of the agenda-setting theoretical model is the transfer of topic salience from the media agenda to the public agenda. Sports leagues need to have their games properly positioned in the television programming schedule to assist their transfer of salience effort and help maximize their national popularity. A sports television programming schedule can be improved with an understanding of the fundamental structural and individual factors that influence audience media exposure. This article contends that the Major League Baseball on Fox programming schedule can be improved through three suggestions: (1) increasing exposure by having more games on the Fox over-the-air broadcast channel that is available in approximately 32 million more households than the Fox Sports One cable channel; (2) having games at a consistent placement in the programming schedule to increase viewers' awareness and enhance that program and channel being a part of their repertoire to capitalize on their initial ritualized viewing; and (3) allowing all Major League Baseball teams to appear more often on Fox and Fox Sports One, eliminating regionalized broadcasts, and implementing a flexible schedule to provide more meaningful game matchups to capitalize on the audience's advanced degree of instrumental viewing.